Development of Welding Technology in the Future: Analysis of Trends and Impacts on Industry and the Environment - Hamzah Hamzah (Collaborate Engineering Daily Book Series, 2023)
Welding combines two or more materials, especially metals, using heat or pressure. Welding is important in various industries, such as automotive, construction, manufacturing, and aerospace. This study aims to analyze trends and developments in welding technology in the future based on the latest data and sources. The research method used is trend analysis, which identifies patterns or directions of change of a variable or phenomenon based on historical data or predictions. The data was collected from web search results. The data is analyzed by classifying based on the type of welding. These factors influence the development of welding, new technologies related to welding, and the challenges and opportunities faced by the welding industry. The research results show that various factors, such as industrial needs, technological advances, environmental issues, and government regulations, influence the development of welding in the future. Some examples of welding technologies that will develop in the future are the use of robotics and artificial intelligence to automate the welding process and improve accuracy and safety, the development of Friction stir welding techniques to combine metals that are difficult to weld, such as aluminium, magnesium, copper, and titanium, and the application of hybrid welding techniques that combine two or more types of welding to obtain optimal results, such as laser-arc welding or laser-friction welding. This research also discusses the social and economic impacts of future developments in welding, especially related to job availability, labour skills, and community welfare. In addition, this study provides suggestions for further research or for welding industry practitioners, such as conducting further research on the environmental impact of future welding developments, developing welding technologies that are environmentally friendly, energy-efficient and sustainable, and improving cooperation between related parties in the welding industry.